The struggle for past glories: Pope Pius XI‟s use of terminology to combat anti-clericalism - Weickert, Amanda (Kansas State University. Dept. of History, 2013)
In 1936 Pope Pius XI published Vigilanti Cura, an encyclical letter that criticized the morality of the motion picture industry. Though the terms certamen and crusade do not mean the same thing, there were multiple instances where Pius XI had certamen officially translated into “holy crusade” in multiple languages within his encyclicals, including Vigilanti Cura. One possible reason for this is that the nineteenth century saw a significant rise in popularity of the Crusades, possibly influencing Pius’s view of his social and religious campaigns. The encyclical Vigilanti Cura uses the term crusade multiple times, implying Pius’s conviction that the campaign against the film industry was exactly that. Along with trying to associate his campaigns with the medieval Crusades to increase support and enthusiasm for them, Pope Pius XI was also trying to associate the enthusiasm for the medieval Crusades with the Catholic Church, taking advantage of the positive attitude toward righteous action and using it for his own ends.
Keywords: Pope Pius XI; Vigilanti Cura; Motion picture industry; Crusades; Certamen